Development of adjuvant for oral cholera vaccine prepared from combined vibrio cholerae antigens - Parairo, Julieta R.
Liposomes were prepared from bovins brain sphingomyelin and cholesterol. They were reinforced by incorporation of osmium tetroxide to prevent their immediate degradation inside the host. Combined V. cholerae antigens (LPS, CHA and P) were orally administered to experimental rats either as free or osmicated, liposome-entrapped vaccine. A total of 70 experimental rats were utilized in experiments comparing the immune responses of rats to liposome-entrapped vaccine, free vaccine, empty liposomes, or placebo, and to vaccines where the lipid or antigen levels were reduced. The animals were fasted overnight, then each was fed with 2 ml of 5% NaCHO 3 to lower thegastric acidity. Immediately after feeding with NaHCO 3, they were fed with either cholera vaccines or placebo. Results of serum ELISA revealed that liposomes can localized the immune responses to the intestinal mucosa, thereby preventing unnecessary stimulation of the serum antibody response. Osmicated liposomes displayed adjuvant properties in terms of higher response to oral cholera antigens as measured through the appearance of specific antibody-producing cells in the intestinal mucosa. The liposomes themselves did not evoke non-specific polyclonal stumulation of B cells. Lowered levels of cholera antigens resulting to higher lipid: antigen ratios enhanced adjuvanticity. Liposomes were easy to prepare, simple to be administered orally and thus suitable as adjuvant for oral cholera vaccines prepared from combined, refined antigens.